Cleaning in the Shadow of the Law? Bargaining, Marital Investment, and the Impact of Divorce Law on Husbands' Intra-Household Work - Jennifer Louise Roff (Institute of Labor Economics (IZA), 2017)
Previous literature has established that unilateral divorce laws may reduce female household work. As shown by Stevenson (2007), unilateral divorce laws may affect overall marital investment. In addition, if unilateral divorce has differential costs by gender, then unilateral divorce may impact household work by gender through bargaining channels. However, little research has examined how divorce laws may affect males' household production and the gender distribution of household work. To examine this issue, I use data on matched couples from the PSID and exploit variation over time in state divorce laws. This research indicates that unilateral divorce laws lead to a decrease in marital investment, as measured by both males and females' household work. The evidence also supports a bargaining response to divorce laws, as fathers in states without joint custody laws show a significantly higher share of household work with unilateral divorce than those in states with joint custody laws, consistent with a relatively higher cost of marital dissolution among fathers who stand to lose custody of their children.
Keywords: J12; J22; 330; divorce law; household bargaining; marriage